Optimizing Battery Storage for Minimizing Forecast Errors in Wind Power Systems - Van der Merwe, Schalk Willem (Stellenbosch : Stellenbosch University, 2025)
van der Merwe, S. W. 2025. Optimizing Battery Storage for Minimizing Forecast Errors in Wind Power Systems. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/38dabddf-409e-4f19-8cb1-cf8dbff39ab5